Creating Noble Morals through the Al-Quran Education Park in Ciberes Village - M. Ibnu Muzakir (Jurnal Pengabdian Masyarakat (Bisma), 2023)
AbstractWith the decline in morals towards children today, it is necessary to get gentle educational touches from both parents, without using physical or psychological violence in order to create future generations of Muslims who have noble morals. "As an effort to create an Islamic young generation, we must start from understanding the true Islamic Aqeedah. The beginning of strengthening this aqidah is by animating and applying the shahada sentence, namely I testify that there is no God who must be worshiped but Allah and the Prophet Muhammad is the Messenger of Allah. The logical consequence of this shahada sentence is to apply Islamic teachings in our daily lives. Because this creed sentence will also be held accountable later in the hereafter. Therefore, in order to create an Islamic generation and motivate the importance of education for the children of Darunnajah University Jakarta students, the KKN carries out activities such as teaching the Koran, how to pray, doing ablutions and other activities.